Praktyka szacowania kosztu kapitału - doświadczenia amerykańskie i brytyjskie a tendencje panujące w Polsce - Byrka-Kita, Katarzyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
This paper presents the results of cost-of-capital surveys conducted on the developed markets against the results of survey carried out among Polish managers. The results show close alignment among American and British managers on the use common theoretical frameworks and on many aspects of estimation. However on the Polish market the tendencies are different - there is a substantial gap between cost-of-capital theory and the procedures applied by the Polish managers. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 1, s. 98-105